Драматична поема «Одержима»: новий етап становлення діалогу у творчості Лесі Українки - Баранова, І. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the formal component of Lesya Ukrainka’s dramatic poem «Obsessed». The peculiarities of the dominant’s content formal expression are discovered. Much attention is paid to the constructive principles of dramatic dialogue (agon, stichomythia, gnome, etc).